The Incredible Shrinking Man in Paul Auster’s Report from the Interior: The Film and the Myths - Marie GOURRUT (E-REA)
The Incredible Shrinking Man, one of the two “written films” (quoted in Gonzalès 18) that Auster narrates in Report from the Interior, turns the book, as in The Book of Illusions, into a virtual screen, showing how influential the 1957 Universal Pictures production was to fabricate both Auster’s auctorial identity and his various characters’ identities. The Incredible Shrinking Man exclusively focuses on the physical metamorphosis of the protagonist who is submitted to a sudden, corporeal diminishment, and then on his rebirth at a higher state of consciousness: after dying to his old self, he struggles to survive, overcoming obstacles and trials as he is confined in the cellar of his own house. The plot undeniably recalls the process of regression, the so-called “art of hunger” that most Austerian protagonists experience. It also casts a light on the theme of the depletion of material resources which pervades Auster’s fictions and conveys, in multiple ways, the idea of “a return to origins” as Mircea Eliade, for instance, analyzed it. Carey’s initiatory and transformative adventure, which resembles a fairy tale, explains, at least partly, Auster’s fascination for this genre which has always inspired him, and Auster’s analysis of the film in Report from the Interior unveils his vision on initiation, on life and fiction, along with his obsession with enclosed spaces.